An Indian approach to health & wellbeing of building occupants - Rajratna Jadhav; S R Bhagat
SDG 3 of the United Nations$1 (B2030 Agenda for Sustainable Development relates to good health & wellbeing of people. There are specific sustainable development frameworks for the health and wellbeing of building occupants. This paper compares four such frameworks including two frameworks for sustainable architectural design that have some criteria for achieving health and wellbeing. The paper uses 11 features of WELL v2 framework, which is identified as the most elaborate and stringent of the frameworks, to identify whether or not similar criteria exist in the other frameworks. It is seen that there are several commonalities and differences between the four frameworks. These commonalities and differences are in their approach, structure, criteria and measures of thresholds or levels. Also, all frameworks are rooted in science. However, it is seen that two Indian frameworks are also rooted in Indian philosophy, culture and spirituality which are expressed in some of the criteria. The criteria emerging out of this Indian rootedness can have universal applicability and can contribute toward the creation of a globally applicable framework.s